Sound stress patterns of nouns ending in -ion produced by English education students - Syafrizal Sabaruddin; Sufiyandi; Muhammad Fadhli; Zul Amri (JOALL (Journal of Applied Linguistics and Literature), 2023)
This study investigated the appropriateness and patterns of sound stress on nouns ending in -ion produced by students of English education study program. The research is designed as a descriptive study. There are 40 English students from Universitas Bengkulu and Universitas Negeri Padang who were selected purposively out of 240 students as the research participants. The data was gathered by using a pronunciation test comprises of 40 nouns ending in -ion with the category of 2, 3, 4, and 5 or more syllables. The participants' utterances were recorded in an audio form, then the sound stress was analyzed using the Audacity application. Based on data analysis, it was discovered that: 1) only 34.44% of students produced the sound stress appropriately, while the rest (65.56) did not; and 2) the pattern of sound stress on noun ending in -ion pronounced by the students varied, with the no stress category dominating. It proves that the more syllables of nouns ending in -ion, the more difficult it is for the students to produce sound stress accurately. Finally, the English students are expected to raise their awareness of practicing sound stress, as it is important for the lecturers to provide more chances for the students in the learning activities.